Cervical cancer mortality trends in Caceres - Mato Grosso (2012 - 2019) (Research, Society and Development, 2021)
Objective: to highlight trends of cervical cancer mortality in the municipality of Cáceres and in the state of Mato Grosso in 2012 to 2019. Methodology: This is a descriptive, retrospective and cross-sectional study of deaths from uterine cancer neoplasms, reported from January 1, 2012 to December 31, 2019 in Cáceres, Mato Grosso Brazil. Results and Discussion: From the data analyzed, the age group of 60 to 69 years was the one that presented the highest number of deaths during the study period, and the brown color/race was the one that stood out most among deaths for cervical cancer. A stable trend in cervical cancer mortality rates was identified in Cáceres-MT. Conclusion: It is believed that the results have an influence of socioeconomic factors and of public health policies to women in the country. Thus, it is important to expand actions aimed at women’s health to reduce deaths from highly preventable pathologies such as cervical cancer.